Heat-induced modulation of flavonoid biosynthesis via a LhMYBC2-Mediated regulatory network in oriental hybrid lily - Yang, Jie (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.